KEEFEKTIFAN CERITA BERGAMBAR UNTUK PENDIDIKAN NILAI DAN KETERAMPILAN BERBAHASA DALAM PEMBELAJARAN BAHASA INDONESIA - Umi Faizah (Jurnal Cakrawala Pendidikan, 2009)
AbstractEffectiveness of Picture Stories in Value Education and Language Skills inIndonesian Language Learning. This study aims to investigate the effectiveness ofpicture stories to improve learning achievement in value education (honesty,patience, and religious worship) and language skills (listening and reading) inIndonesian language learning. This study was a quasi-experimental studyemploying the pretest-posttest control group design. The population comprised all114 Year II students of MIN Tempel Sleman Yogyakarta. The sample, selected bythe random sampling technique, consisted of 70 students, divided into theexperimental group and the control group. The results show that (1) the learningachievement in value education of the students in the experimental group is higherthan that of the students in the control group, and (2) the learning achievement inlanguage skills of the students in the experimental group is higher than that of thestudents in the control group. It can be concluded that the use of picture stories iseffective for value education and Indonesian language skills.Keywords: picture stories, value education, language skills